VD_FINDINFO Arrêt / 2013 / 44 vom 23. Juli 2013 - VD Tribunal cantonal (2013)
COMPARAISON DES REVENUS, RENTE D'INVALIDITÉ, DEGRÉ DE L'INCAPACITÉ DE TRAVAIL | 28 al. 2 LAI, 4 al. 1 LAI, 16 LPGA, 6 LPGA, 7 LPGA, 8 LPGA